1994
DOI: 10.1002/cne.903500308
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal and nonpyramidal callosal cells in the striate cortex of the adult rat

Abstract: The aim of this study has been to determine the neuronal types (pyramidal and nonpyramidal) within the rat's visual cortex, which project through the corpus callosum. To this end, the morphology and laminar distribution of callosal cells have been investigated by combining Diamidino Yellow retrograde tracing with intracellular injection of Lucifer Yellow in slightly fixed tissue slices. The visual callosal projection arises from pyramidal cells of diverse morphology in layers II to VIb, as well as from several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…Similar results were also found in marmoset monkeys (Baldauf 2005;Bourne et al 2005). The non-pyramidal neuronal population that contains NFPs Brain Struct Funct (2011) 216:183-199 195 includes most likely star pyramids (Peters and Kara 1985;Cipolloni and Pandya 1991;Martínez-García et al 1994; Van der Gucht et al 2007). Previous studies on carnivores and primates located SMI-32 exclusively in a subset of pyramidal neurons known to be a class of long association projection neurons (Hof et al , 1996cNimchinsky et al 1996; Van der Gucht et al 2001.…”
Section: Nf-l Content and Myelinationsupporting
confidence: 80%
“…Similar results were also found in marmoset monkeys (Baldauf 2005;Bourne et al 2005). The non-pyramidal neuronal population that contains NFPs Brain Struct Funct (2011) 216:183-199 195 includes most likely star pyramids (Peters and Kara 1985;Cipolloni and Pandya 1991;Martínez-García et al 1994; Van der Gucht et al 2007). Previous studies on carnivores and primates located SMI-32 exclusively in a subset of pyramidal neurons known to be a class of long association projection neurons (Hof et al , 1996cNimchinsky et al 1996; Van der Gucht et al 2001.…”
Section: Nf-l Content and Myelinationsupporting
confidence: 80%
“…Recent findings suggest that they are important developmentally (Ogawa et al, 1995); however, their fate in the adult cortex has not been resolved. Only a few authors have reported on CR cells in the adult brain (Condé et al, 1994;Martínez-García et al, 1994). Indeed, we have identified CR cells only in relatively young animals (7-to 9-d-old).…”
Section: Cr Cellsmentioning
confidence: 66%
“…Martínez-García et al (1994) found that some cells in the inner half of layer I project to the contralateral visual cortex. Therefore, it may be that some of the cells we classify as cells with descending axons provide input to distant regions in addition to the collateral inputs seen in deeper cortical layers.…”
Section: Cells With Descending Axonsmentioning
confidence: 99%
“…Our fMRI results and LFP latency analyses suggest that lowfrequency activity propagates downstream from ipsilateral dDG/ dHP to ipsilateral VC via the ipsilateral lateral EC (LEC) (5), before reaching contralateral VC through the corpus callosum (40,56) to finally terminate in the LGN and SC via corticothalamic and corticocollicular descending projections. The medial EC (MEC) may not actively participate in our observed responses because dHP is functionally coupled with LEC, not MEC, to establish functional gradients along the dorsoventral hippocampal axis (8).…”
Section: Discussionmentioning
confidence: 98%